Social Science Print Comic Media with Contextual Approach and Its Effect on Literacy Ability of Left-handed Students - Ni Wayan Nik Sri Artini; I Wayan Sujana (Indonesian Journal Of Educational Research and Review, 2022)
The learning process for left-handed students still uses printed learning media designed for non-handed people. It causes students to be less comfortable in learning. This study aims to develop social studies learning media in printed comics designed for left-handed students. This research is Research and Development with Hannafin and Peck model. Subjects included content, design, learning media experts, and 15 left-handed students. The data in this study were collected using the method of tests, questionnaires, observation, and unstructured interviews. Data analysis was performed using quantitative descriptive analysis techniques, qualitative descriptive research, and inferential statistical analysis (dependent t-test). The assessment of content, design, and instructional media experts obtained percentages of 98.21%, 95.83%, and 92.50% with very good qualifications. Student trials, namely individual trials, small group trials, and field trials, each obtained a percentage of 92.50%, 91.67%, and 91.17% with very good qualifications. The effectiveness test results were conducted (pre-test) with an average score of 78.9 and (post-test) with an average score of 84.3. The results of hypothesis testing with dependent t-test showed that the value of tcount (8.4371) was greater than ttable (2.475) at N=15, with a significance level of 5% (0.005). It means that H0 is rejected and H1 is accepted, so printed comics based on a contextual approach effectively improve the literacy skills of fourth-grade elementary school students.